2019
DOI: 10.23960/jbekh.v5i2.53
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN EKSTRAK ETANOL JAHE MERAH (Zingiber Officinale Roxb var Rubrum) TERHADAP KUANTITAS DAN KUALITAS SPERMATOZOA MENCIT JANTAN (Mus musculus L.) YANG DIINDUKSI PARAQUAT DIKLORIDA

Abstract: Paraquat is one of the chemicals that contributes to increasing pollution Indonesia. The careless use of paraquat can increase production of ROS (Reactive Oxygen Species), resulting in damage to a wide range of vital organs and reproductive system disorders such as infertility. ROS in the body can be captured by antioxidants. Red Ginger contains high antioxidants because there are active phenolic compounds such as gingerol, shagaol, zingeron, ginggerdiol, and zingibren which are proven to protect body cells fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The herbicide paraquat has the effect of increasing free radicals and reactive oxygen species (ROS) in the body, which damages the hypothalamic-pituitary-testicular axis's communication (HHT). Oral administration of paraquat at a dose of 20 mg / Kg BB can diminish the quality of spermatozoa in male rats (Anggraini et al, 2018). In previous studies, paraquat has been shown to reduce spermatozoa quality, whereas in this study paraquat was able to reduce FSH levels and the number of sertoli cells in male Wistar mice, indicating that this study is consistent with previous research.…”
Section: Disscussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The herbicide paraquat has the effect of increasing free radicals and reactive oxygen species (ROS) in the body, which damages the hypothalamic-pituitary-testicular axis's communication (HHT). Oral administration of paraquat at a dose of 20 mg / Kg BB can diminish the quality of spermatozoa in male rats (Anggraini et al, 2018). In previous studies, paraquat has been shown to reduce spermatozoa quality, whereas in this study paraquat was able to reduce FSH levels and the number of sertoli cells in male Wistar mice, indicating that this study is consistent with previous research.…”
Section: Disscussionsupporting
confidence: 92%
“…The toxicity of paraquat administration orally dose 20 mg/kg BW in male mice, it is possible to reduce sperm quality (Anggraini et al, 2018). Paraquat has the effect of changing the histological structure of the testes and causing spermatogenesis failure in male Wistar rats (Wasiu & Abdulfatai, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, damage to the mitochondrial membrane of sperm cells would reduce the amount of ATP needed for sperm movement, damaged the DNA structure, and led to sperm cell death. Decreased sperm motility could also be caused by sperm maturation in the epididymis (Anggraini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Taurine could also stimulate testosterone secretion in both in vivo and in vitro conditions (Yang et al, 2010). Testosterone functioned to control the spermatogenesis process, increased the Sertoli cells, and played a role in determining the quality of spermatozoa (Anggraini et al, 2019). Taurine, which was non-enzymatic, had a positive effect on spermatozoa during cryo conservation due to more minor damage to male gametes.…”
Section: Introductionmentioning
confidence: 99%